Agar-Paraffin Double Embedding Over Conventional Embedding for Minute Oral Biopsies- Cohort Study - S.Sandhya1, Pratibha Ramani2, Herald J Sherlin3, Gheena.S4, Abilasha R5, Gifrina Jayaraj6 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Agar-Paraffin double embedding technique is a simple technique that combines the advantages of both the embedding material. It preserves the minute tissue biopsies in orientation and holds them together from getting lost. Oral biopsies, being most commonly small incisional tissues, have to be preserved all through the processing and embedding to ensure optimal visualization of all the mucosal layers without compromise. In the present study, samples were divided into two groups: Group A: Agar-paraffin double embedding (APE) and Group B: conventional paraffin embedding (PE). Tissue samples collected were sectioned into two approximately equal sized bits. Both the bits were simultaneously processed, embedded in two different techniques (APE and PE method). Sections obtained were scored by an observer and analyzed using independent sample t-test (SPSS software version 21) to evaluate the efficacy of agar-paraffin double embedding technique in comparison to the conventional paraffin embedding technique. Agar paraffin embedded tissue was found to be well processed, firm and well preserved. Orientation was comparatively easier and the blocks yielded sections of good quality. They showed no interference with staining and cell morphology was of good clarity. Thus Agar-paraffin embedding technique represents a simple, reliable method that can greatly improve the quality of diagnostic information.